OSTEOMYELITIS OF FEMUR IN A DRUG ADDICTED CHILD - Kirovski, Ilija; Micevska, Vesna; Sofijanova, Aspazija; Bojadzieva, Sonja; Naunova Timovska, Silvana; Jordanova, Olivera (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
One of the serious complications related to intravenous drug use is osteomyelitis. We report a 13-year-old male child with a history of intravenous heroin abuse, who was admitted to the hospital complaining of abdominal pain and pain in the left leg. Anteroposterior roentgenogram and CT scan of the left thigh and femur, confirmed the diagnosis of osteomyelitis. Pus culture was positive for Staphylococcus aureus. Despite extensive antibiotic and anticoagulant therapy, the patient’s clinical status improved very slowly. Surgical procedure was not undertaken. Femoral osteomyelitis due to injection drug use in childhood is an extremely rare and uncommon condition. Intravenous drug abuse, late-onset treatment, and secondary bacterial infection can lead to complications which occurred in the case presented. It is an extremely difficult condition to treat and is a real challenge for physicians. The rapid response and participation of a multidisciplinary team of physicians is of particular importance. Key words : antibiotics, children, femur, osteomyelitis, staphylococcus aureus. https://doi.org/10.55302/JMS2141046k